Evaluation of caries risk assessment practices among dental practitioners in Guangzhou, China: a cross-sectional study - Nie, Ermin; Jiang, Rui; Islam, Rafiqul; Li, Xiang; Yu, Jiali (Frontiers in Oral Health, 2024)
IntroductionThis cross-sectional study aimed to investigate dental practitioners’ knowledge and practices regarding Caries risk assessment (CRA) in routine clinical practice in Guangzhou, China.MethodsAn online questionnaire was disseminated to dental practitioners to gather socio-demographic information, factors associated with CRA, the implementation of preventive treatment, and the level of awareness regarding personalized preventive treatment in relation to CRA. Statistical analyses included descriptive statistics, Chi-square tests, ANOVA, MANCOVA, linear regression, and scatter plots.Results and discussionOut of the 695 dental practitioners who were contacted, 206 dentists participated in the online survey. However, out of the total number of dentists, 198 were successfully recruited, while the remaining 8 dentists had incomplete data in their questionnaires. 92.4% of dentists provided in-office fluoride treatments, and 73.2% held a strong belief in the correlation between current oral hygiene and tooth cavities. 23.7% of dentists evaluated caries risk on an individual basis, and a significant 41.9% never utilized a particular type of CRA. 53.5% of dentists recommended non-prescription fluoride rinses, whereas 51% advocated prescription fluoride treatments. Significant statistical relationships were found between the use of in-office fluoride and the effectiveness of restorative treatment (P < 0.05). Additionally, a significant association was discovered between the use of a specific form for CRA and the kind of dental school (P < 0.05). The study suggests that a significant number of dental practitioners in Guangzhou, China, do not utilize dedicated assessment forms for CRA in their routine professional activities. These findings highlight the im-portance of encouraging dentists to utilize CRA systems to effectively identify patients who are at risk of acquiring dental caries.